2021
DOI: 10.5483/bmbrep.2021.54.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Myonectin inhibits adipogenesis in 3T3-L1 preadipocytes by regulating p38 MAPK pathway

Abstract: In current times, obesity is a major health problem closely associated with metabolic disease such as diabetes, dyslipidemia, and cardiovascular disease. The direct cause of obesity is known as an abnormal increase in fat cell size and the adipocyte pool. Hyperplasia, the increase in number of adipocytes, results from adipogenesis in which preadipocytes differentiate into mature adipocytes. Adipogenesis is regulated by local and systemic cues that alter transduction pathways and subsequent control of adipogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Protein phosphorylation (GO:0006468) and cellular response to insulin stimulus (GO:0032869) were enriched in the MetO-treated group by GO analysis (Figure 4c). The MAPK signaling pathway was enriched in the MetO-treated group compared with control group by KEGG analysis (Figure 4d), which correlated with previous studies on adipogenesis (Park et al, 2021). ERKs, JNKs, and p38 of the MAPK/ERK pathway are detected by western blot analysis.…”
Section: Meto Inhibits Adipocyte Differentiation By Mediating the Map...supporting
confidence: 88%
“…Protein phosphorylation (GO:0006468) and cellular response to insulin stimulus (GO:0032869) were enriched in the MetO-treated group by GO analysis (Figure 4c). The MAPK signaling pathway was enriched in the MetO-treated group compared with control group by KEGG analysis (Figure 4d), which correlated with previous studies on adipogenesis (Park et al, 2021). ERKs, JNKs, and p38 of the MAPK/ERK pathway are detected by western blot analysis.…”
Section: Meto Inhibits Adipocyte Differentiation By Mediating the Map...supporting
confidence: 88%
“…Furthermore, they showed that MN has an inhibitory effect on adipogenesis through the regulation of the p38 mitogen-activated protein kinase (MAPK) pathway and C/EBP homologous protein (CHOP). These results suggest that MN may be a new therapeutic target for obesity prevention [ 90 ] and required for metabolic homeostasis [ 91 ]. In addition, there are various other myokines that are secreted by skeletal muscle and influence pancreatic, hepatic, and adipose tissue and that are thought to affect glucose tolerance through various mechanisms.…”
Section: Intermittent Hypoxia and Cytokinesmentioning
confidence: 99%
“…Adipogenesis of 3T3-L1 induced by dexamethasone and IBMX [41] activates adipogenic transcription factors, PPARγ and C/EBPα [42]. During the differentiation of 3T3-L1 fibroblasts to adipocytes, PPARγ and C/EBPα regulate the expression of adipogenic genes such as GLUT-4, FAS, and adiponectin [43,44].…”
Section: Discussionmentioning
confidence: 99%